INTEGRATION OF RAHMATAN LIL'ALAMIN VALUES TO STRENGTHEN NATIONAL CHARACTER: A MULTI-SITE STUDY IN SMA PLUS SE KOTA MEDAN - Domu Hamunangan Harahap; Siti Halimah; Wahyudin Nur Nasution (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
The Independent Learning Curriculum also places significant emphasis on developing students' character. Values ​​such as mutual cooperation, integrity, independence, and a sense of social responsibility are instilled through various learning activities designed to reflect real-world experiences. The relevance of instilling educational values ​​in relation to education, particularly Islamic education, is evident in the verse 7 of Surah Al-Anbiya' (The Holy Quran), which has profound implications for instilling these values. Education not only transfers knowledge but also instills the values ​​of rahmatan lil-'alamin (blessings for all the universe). This research is expected to provide a comprehensive overview of how the integration of Rahmatan Lil 'Alamin values ​​can be implemented in Islamic Religious Education (Islamic Religious Education), particularly in strengthening students' national character. The results of this study are expected not only to contribute theoretically to the development of character education studies based on moderate Islamic values, but also to serve as a practical reference for educators, educational units, and policymakers in designing relevant, applicable, and contextual Islamic Religious Education (PAI) learning models in accordance with the spirit of the Independent Curriculum. The purpose of this research is to analyze the integration of rahmatan lil 'alamin values ​​to strengthen national character. This type of research is field research, where the key instrument is going into the field to conduct direct observations of a phenomenon.